ERK MAPK signaling pathway inhibition as a potential target to prevent autophagy alterations in Spinal Muscular Atrophy motoneurons - Alba Sansa; Maria P. Miralles; Maria Beltran; Ferran Celma-Nos; Jordi Calderó; Ana Garcera; Rosa M. Soler (Cell Death Discovery, 2023)
Abstract Spinal Muscular Atrophy (SMA) is a severe genetic neuromuscular disorder that occurs in childhood and is caused by misexpression of the survival motor neuron (SMN) protein. SMN reduction induces spinal cord motoneuron (MN) degeneration, which leads to progressive muscular atrophy and weakness. The link between SMN deficiency and the molecular mechanisms altered in SMA cells remains unclear. Autophagy, deregulation of intracellular survival pathways and ERK hyperphosphorylation may contribute to SMN-reduced MNs collapse, offering a useful strategy to develop new therapies to prevent neurodegeneration in SMA. Using SMA MN in vitro models, the effect of pharmacological inhibition of PI3K/Akt and ERK MAPK pathways on SMN and autophagy markers modulation was studied by western blot analysis and RT-qPCR. Experiments involved primary cultures of mouse SMA spinal cord MNs and differentiated SMA human MNs derived from induced pluripotent stem cells (iPSCs). Inhibition of the PI3K/Akt and the ERK MAPK pathways reduced SMN protein and mRNA levels. Importantly, mTOR phosphorylation, p62, and LC3-II autophagy markers protein level were decreased after ERK MAPK pharmacological inhibition. Furthermore, the intracellular calcium chelator BAPTA prevented ERK hyperphosphorylation in SMA cells. Our results propose a link between intracellular calcium, signaling pathways, and autophagy in SMA MNs, suggesting that ERK hyperphosphorylation may contribute to autophagy deregulation in SMN-reduced MNs.